Fluorescent-Labeled Amino Acid–Antibiotic Conjugates - Tiwari, Anand D.; Panda, Siva S.; Asiri, Abdullah M.; Hall, C. Dennis; Katritzky, Alan R. (Synthesis, 2014)
Benzotriazole-mediated synthesis provides novel fluorescent-labeled amino acid–quinolone antibiotic conjugates in good yields with retention of chirality. The photophysical properties of all the fluorescent-labeled antibiotic conjugates were determined.
Keywords: antibiotics; amino acid; drug design; microwave assisted reaction; fluorescent labels